2021
DOI: 10.35316/edupedia.v5i2.1200
|View full text |Cite
|
Sign up to set email alerts
|

Peran Guru Profesional Sebagai Fasilitator Dan Komunikator Dalam Kegiatan Belajar Mengajar

Abstract: the role of professional teachers in carrying out activities as educators obligate to have a capability in the learning plan, performing the learning activities, and evaluate learning outcomes. Professional teachers have to own competence, both personal competence, pedagogical competence, and social competence. There are several important roles for a professional teacher that are as a leader, guide, supervisor, counselor, expeditor, motivator, facilitator, and communicator. The role of the teacher as a facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
24

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 0 publications
0
5
0
24
Order By: Relevance
“…Based on the elaboration of the findings above, it can be inferred that the programs designed and the results of data collection that have been carried out by researchers are similar. The teacher as a communicator is the teacher's way of conveying something to children (Arfandi & Samsudin, 2021;Ratminingsih et al, 2018). From the results shown in the observation notes and interviews, it was found that the teacher already had some knowledge about the materials that needed to be mastered and then delivered to the children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the elaboration of the findings above, it can be inferred that the programs designed and the results of data collection that have been carried out by researchers are similar. The teacher as a communicator is the teacher's way of conveying something to children (Arfandi & Samsudin, 2021;Ratminingsih et al, 2018). From the results shown in the observation notes and interviews, it was found that the teacher already had some knowledge about the materials that needed to be mastered and then delivered to the children.…”
Section: Discussionmentioning
confidence: 99%
“…Professional teachers act as communicators and motivators for children. Teachers as communicator can be interpreted as planner, implementer, and creator of a communicative condition in activities carried out by children to assist teachers in measuring children developmental achievement (Arfandi & Samsudin, 2021;Scanlon et al, 2022). Teachers as motivator refers to the ability in guiding children to receive the process of activities, helping children to become active and excited and growing their interest to the activities so that the purpose of the activities could be achieved optimally (Fen & Poh, 2015;Umasugi, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Menurut Undang-Undang nomor 14 tahun 2005 pasal 10 ayat (8), guru memiliki kompetensi pedagogik, kompetensi kepribadian, kompetensi sosial, dan kompetensi profesional. Dalam koteks tersebut guru menjalankan tugas sebagai pendidik, pengajar, pembimbing, pengarah, pelatih, penilai bagi siswa dalam mencapai tujuan-tujuan pembelajaran dan pendidikan (Kusnandar 2009;Arfandi & Samsudin 2021). Sebagai seorang professional maka seorang guru melaksanakan tugas-tugas tersebut.…”
Section: Landasan Filosofi Merdeka Belajarunclassified
“…Selain itu guru juga berkedudukan sebagai agen pembelajaran untuk mencapai tujuan dan meningkatkan pendidikan nasional. Sebagai guru professional dalam kegiatan belajar mengajar, seorang guru tidak hanya menjalankan tugas dan fungsinya sebagai orang yang ahli ilmu pengetahuan (transfer of knowledge) akan tetapi juga seorang guru bisa berfungsi untuk bisa menanamkan nilai (value) serta bisa membangun karakter (character building) peserta didik secara berkelanjutan dan berkesinambungan (Arfandi & Samsudin, 2021).…”
Section: Hasil Dan Pembahasanunclassified